Praktik Kepemimpinan Tranformasional Dalam Organisasi Islam (Studi Tentang Kepemimpinan Umar Bin Khattab Dalam Peristiwa Pembebasan Ibukota Persia – Madain) - Tri Ahmad Faridh (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
This study aims to describe the practice of transformational leadership, specifically regarding the practice of the components of transformational leadership applied by Umar bin Khattab in the event of the liberation of the Persian capital-Madain. This study method is qualitative-non-experimental-descriptive. The data collection used the documentation method with secondary data sources, namely the life history of Umar bin Khattab written by historians such as Muhammad Husain Haekal, Ali Muhammad AshShalabi, and Musthafa Murad. Data analysis used the Miles and Huberman model, with the components theory of transformational leadership developed by Bass and Avolio as a theoretical framework. The findings show that the leadership components of Umar bin Khattab were used in overcoming pessimistic situations due to Persian forces. Umar showed a leadership that was able to change the great vision of Muslims in facing Persian rule and had clear steps to realize it, was consistent in realizing dreams, was able to arouse and maintain the motivation of members by attending especially in difficult situations, and providing guidance to get out of difficulties. In the event that he cannot attend in person, long-distance communication is maintained. He appointed representatives who were believed to be able to transform leadership at lower levels. Umar succeeded in reviewing opportunities to improve the situation in ways that were outside the habits of his predecessors, one of which was by using an army of apostates who had repented. Thus Umar bin Khattab applied the four components of transformational leadership, namely idealized influence, inspirational motivation, individualized consideration, and intellectual stimulation.